ANTIUROLITHIC ACTIVITY OF BERBERIS TRIFOLIATA EXTRACT ON INDUCED UROLITHIASIS IN RATS BY ZINC DISC IMPLANTATION - Pérez-Hernández, Raymundo Alejandro; Treviño-Moreno, Silvia Guadalupe; Arévalo- Martínez, Gilberto; Sánchez -García, Eduardo; Leos-Rivas, Catalina; Rivas-Morales, Catalina (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: In clinical therapy, there is no satisfactory drug available for treatment of urolithiasis, especially for the prevention of their recurrence. The aim of this work was to evaluate in vivo antiurolithic activity of methanolic extract of Berberis trifoliata leaves.Material and methods: Urolithiasis was induced in Wistar rats by zinc disc implantation in urinary bladder. Upon postsurgical recovery, different doses of the methanolic extract of B. trifoliata leaves (50, 100 and 150 mg/kg body weight) were administered orally to zinc disc implanted rats for a period of 20 days. Antiurolithiatic activity was evaluated by measuring the difference between the weight of the implanted zinc discs at the time of implantation and the final weight of the dried calculi taken out from the bladder at the end of the 20 days period of treatment. Results: Extract of B. trifoliata significantly reduced calculi deposition around the implanted zinc disc at all doses (50, 100, and 150 mg/kg). Conclusion: Treatment with methanolic extract of B. trifoliata is useful agent against the kidney stone formation.